Advancement in the Design and Performance of Sustainable Asphalt Pavements Proceedings of the 1st GeoMEast International Congress and Exhibition, Egypt 2017 on Sustainable Civil Infrastructures (Sustainable Civil Infrastructures,, 2018)
This volume on "Advancement in the Design and Performance of Sustainable Asphalt Pavements" includes a collection of research and practical papers from an international research and technology activities on Mixture Design Innovation, Structural Pavement Design, Advancement in Production and Construction, Climate Changes and Effects on Infrastructure, Green Energy, Technology and Integration. The volume constitutes an important contribution in view of the urgent need to develop materials, designs, and practices to ensure the sustainability of transportation infrastructure. This volume is part of the proceedings of the 1st GeoMEast International Congress and Exhibition on Sustainable Civil Infrastructures, Egypt 2017.